Diet-Related Metabolic Perturbations of Gut Microbial Shikimate Pathway-Tryptamine-tRNA Aminoacylation-Protein Synthesis in Human Health and Disease. (March 2019) - Paley, Elena L
Human gut bacterial Na(+)-transporting NADH:ubiquinone reductase (NQR) sequence is associated with Alzheimer disease (AD). Here, Alzheimer disease-associated sequence (ADAS) is further characterized in cultured spore-forming Clostridium sp . Tryptophan and NQR substrate ubiquinone have common precursor chorismate in microbial shikimate pathway. Tryptophan-derived tryptamine presents in human diet and gut microbiome. Tryptamine inhibits tryptophanyl-tRNA synthetase (TrpRS) with consequent neurodegeneration in cell and animal models. Tryptophanyl-tRNA synthetase inhibition causes protein biosynthesis impairment similar to that revealed in AD. Tryptamine-induced TrpRS gene-dose reduction is associated with TrpRS protein deficiency and cell death. In animals, tryptamine treatment results in toxicity, weight gain, and prediabetes-related hypoglycemia. Sequence analysis of gut microbiome database reveals 89% to 100% ADAS nucleotide identity in American Indian (Cheyenne and Arapaho [C&A]) Oklahomans, of which ~93% being overweight or obese and 50% self-reporting type 2 diabetes (T2D). Alzheimer disease-associated sequence occurs in 10.8% of C&A vs 1.3% of healthy American population. This observation is of considerable interest because T2D links to AD and obesity. Alzheimer disease-associated sequence prevails in gut microbiome of colorectal cancer, which linked to AD. Metabolomics revealed that tryptamine, chorismate precursor quinate, and chorismate product 4-hydroxybenzoate (ubiquinone precursor) are significantly higher, while tryptophan-containing dipeptides are lower due to tRNA aminoacylation deficiency in C&A compared with non-native Oklahoman who showed no ADAS. Thus, gut microbial tryptamine overproduction correlates with ADAS occurrence. Antibiotic and diet additives induce ADAS and tryptamine. Mitogenic/cytotoxic tryptamine cause microbial and human cell death, gut dysbiosis, and consequent disruption of host-microbe homeostasis. Present analysis of 1246 participants from 17 human gut metagenomics studies revealed ADAS in cell death diseases.